METALLURGICAL AND MATERIALS TRANSACTIONS A- PHYSICAL METALLURGY AND MATERIALS SCIENCE. (Ohio Metallurgical Society of AIME, 1990)
Focuses on physcal metallurgy and materials science, with a special emphasis on relationships among the processing structure and properties of materials.
Keywords: Metallurgy